NUEVOS ARGUMENTOS EN FAVOR DE LA TRANSFERENCIA DE ROTODACTYLUS, ICNOGENERO REPTILIANO TRIASICO, DE LOS "CROCODILOIDES" (ARCHOSAURIA) A LOS "LACERTOIDES" (INCERTAE SEDIS) (Ameghiniana, 2013)
In the light of the existence of a Liassic footprint with a rotodactyloid digit V, the removal of Botodactulus from the "Crocodiloids" auctorurn (Pseudosuchians ) and its formal transference to the "Lacertoíds" (lncertae sedis: Lacertilia or Araeoscelidia), is proposed. 2) An explanation for the gait of the author of the trackways of that name is proposed. It should pertain to the "trote reptiliano" (reptilían trot) or "calperpétíco' of Magne de la Croix' classification; that is, an advanced reptilian gait (performed at present by some Lacertilia), but former, phylogenetically speaking, than that of Crotaphytus. 3) A new ichno-genus (Neorotodaciulus) and a new ichno-specíes (N. leonardii) are proposed for the Liassic footprint from Neuquén (Piedra Pintada Formation).